2014
DOI: 10.1016/j.expneurol.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute inactivation of the contralesional hemisphere for longer durations improves recovery after cortical injury

Abstract: A rapidly growing number of studies using inhibition of the contralesional hemisphere after stroke are reporting improvement in motor performance of the paretic hand. These studies have used different treatment onset time, duration and non-invasive methods of inhibition. Whereas these results are encouraging, several questions regarding the mechanisms of inhibition and the most effective treatment parameters are currently unanswered. In the present study, we used a rat model of cortical lesion to study the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…did not differ between 9 and 14 days after the lesion induction, respectively. This result corroborates previous studies using cortical compression or endothelin-1 to induce a restricted ischemic infarct to the S1 cortex which showed that cell death increase during the early postlesion days, is at a maximum at 3–5 days and does not evolve over the subsequent days and weeks [31], [32], [33], [34].…”
Section: Discussionsupporting
confidence: 92%
“…did not differ between 9 and 14 days after the lesion induction, respectively. This result corroborates previous studies using cortical compression or endothelin-1 to induce a restricted ischemic infarct to the S1 cortex which showed that cell death increase during the early postlesion days, is at a maximum at 3–5 days and does not evolve over the subsequent days and weeks [31], [32], [33], [34].…”
Section: Discussionsupporting
confidence: 92%
“…However, the contralesional dendritic growth in layer V pyramidal neurons that we have observed has no known benefit (83), and contralesional M1 activity can have disruptive influences on paretic limb function (47, 126,134,141). Sprouting can also be maladaptive.…”
Section: Reviewsmentioning
confidence: 87%
“…These implications are clinically important because the phenomenon of “learned nonuse,” or heightened reliance on the good limb after stroke, is a common sequelae to hemiparesis, but may hinder circuit repair and motor recovery. The effect of the contralateral cortex on recovery was also shown to be negative in blocking study: muscimol inactivation of the contralesional cortex for 3–14 days improves behavioral outcome (Mansoori et al, 2014). This data indicates that in different animal models of stroke, the contralateral (to the stroke) cortex has been shown to both mediate recovery and to impede recovery.…”
Section: Contralateral Cortical Axonal Sprouting After Strokementioning
confidence: 99%